2016
DOI: 10.1371/journal.pone.0162174
|View full text |Cite
|
Sign up to set email alerts
|

Study on Interactions between the Major Apple Valsa Canker Pathogen Valsa mali and Its Biocontrol Agent Saccharothrix yanglingensis Hhs.015 Using RT-qPCR

Abstract: The mechanism of biocontrol agent Saccharothrix yanglingensis Hhs.015 action against Valsa mali, a major apple Valsa canker pathogen, was examined using a novel, sensitive (minimum detection limit 100 pg/μL) and reliably RT-qPCR technique. Prior to lesion formation, total concentration of V. mali in the bark showed a significant decrease (p<0.05) after 24 h of Hhs.015 treatment. This was more pronounced at 48 and 96 h post treatment. After lesion formation, levels of V. mali remained constant at the boundary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The inhibition ratio of T4SB028 against Alternaria solani, Valsa malicola, and Valsa mali was 67.06, 64.20, and 70.55%, respectively. This had accordance with the previous study (le Roes-Hill and Meyers, 2009;Fan et al, 2016;Law et al, 2017). This result demonstrated the potential of strains Streptomyces sp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The inhibition ratio of T4SB028 against Alternaria solani, Valsa malicola, and Valsa mali was 67.06, 64.20, and 70.55%, respectively. This had accordance with the previous study (le Roes-Hill and Meyers, 2009;Fan et al, 2016;Law et al, 2017). This result demonstrated the potential of strains Streptomyces sp.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, a total of 150 endophytic actinobacteria were isolated from three medicinal plant species (Annonaceae squamosa, Camptotheca acuminata, and Taxus chinen), and 72.4% of them showed inhibition against more than one indicator microorganism, including Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Candida albicans, and Aspergillus niger (Wu et al, 2009). In addition, endophytic actinobacteria were antagonistic against Pythium aphanidermatum and significantly promoted plant growth and reduced the crown and root rot of cucumber that was caused by the Pythium aphanidermatum in vitro condition (El-Tarabily et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have shown that Sy Hhs.015 sterile fermentation filtrate can inhibit the growth of mycelium and conidia germination of Vm , and abnormal mycelia and cytoplasmic extravasation can be observed. Field experiments has shown that the relative control efficiency of apple trees infected with Vm after Sy Hhs.015 treatment was 61.29%, which was equivalent to that of treatment with difenoconazole and tebuconazole [ 11 ]. Studies have shown that Sy Hhs.015 can produce heteroauxin, chitinase, proteinase and glucanase, and the active substances isoflavones and pentamycin have been extracted from its fermentation broth [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two Chitinase 1 genes (KUI66287.1, KUI69708.1) among the DEGs were significantly downregulated (log2FC = -2.21). Meanwhile, chitinase, proteinase and glucanase produced by Sy Hhs.015 also destroyed the cell wall structure of Vm (Fan et al, 2016). Combining these factors, it can be speculated that Sy Hhs.015 damaged the cell wall of Vm and cell wall formation and cell division were blocked, resulting in the inhibition of Vm growth.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments has shown that Sy Hhs.015 sterile fermentation filtrate can inhibit the growth of mycelium and conidia germination of Vm, and abnormal mycelia and cytoplasmic extravasation can be observed. Field experiments has shown that the relative control efficiency of apple trees infected with Vm after Sy Hhs.015 treatment was 61.29%, which was equivalent to that of treatment with difenoconazole and tebuconazole (Fan et al, 2016). Studies have shown that Sy Hhs.015 can produce heteroauxin, chitinase, proteinase and glucanase, and the active substances isoflavones and pentamycin have been extracted from its fermentation broth (Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%